2007 IEEE/RSJ International Conference on Intelligent Robots and Systems 2007
DOI: 10.1109/iros.2007.4399464
|View full text |Cite
|
Sign up to set email alerts
|

Foul 2050: thoughts on physical interaction in human-robot soccer

Abstract: Abstract-The RoboCup community has one definite goal: winning against the human world soccer champion team by the year 2050 [1]. This implies real tackles and fouls between humans and robots and rises safety concerns for the robots and even more important for the human players. Nowadays, similar questions are discussed in the field of physical humanrobot interaction (pHRI), but mainly in the context of industrial and service robotics applications.Our paper is an attempt for a pHRI view on human-robot soccer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
2
14
0
2
Order By: Relevance
“…This is an impressive result, but still more than five times slower than the top speed of a human soccer player. A similar gap regarding kicking velocity has been pointed out by Haddadin et al (2007). They showed that a state-of-the-art robot arm (with a configuration comparable to a human leg) is six times slower than required to accelerate a standard soccer ball to an adequate velocity.…”
Section: Challenges For Actuationsupporting
confidence: 60%
See 1 more Smart Citation
“…This is an impressive result, but still more than five times slower than the top speed of a human soccer player. A similar gap regarding kicking velocity has been pointed out by Haddadin et al (2007). They showed that a state-of-the-art robot arm (with a configuration comparable to a human leg) is six times slower than required to accelerate a standard soccer ball to an adequate velocity.…”
Section: Challenges For Actuationsupporting
confidence: 60%
“…artificial muscles, will be needed. Since soccer is a contact sport leading to physical human-robot interaction (Haddadin et al, 2007), not only direct position control but also approaches for compliant motion, such as impedence control, need to be taken into account. Additionally, the problems of energy efficency and power supply need to be solved.…”
Section: Challenges For Actuationmentioning
confidence: 99%
“…Although being designed as an arm, it has inertial and geometric properties comparable to a human leg ( [11,24]. So we use it as a "model" for the leg of a future humanoid soccer robot throughout, while not claiming that the design is feasible for a leg in general.…”
Section: A Simulation Model For a Humanoid Soccer Robot Legmentioning
confidence: 99%
“…4) and discuss their injury potential for the human and the robot. The discussion is based on a recent paper [24]. There we have analyzed scenes from the FIFA world championship 2006 in detail pretending that one of the players was a robot.…”
Section: Physical Interaction In Human Soccermentioning
confidence: 99%
See 1 more Smart Citation